Operational Management of Islamic Financial Institutions - Sholehuddin (Al-Fadilah: Islamic Economics Journal, 2025)
Islamic Financial Institutions (IFIs) are financial entities that operate based on sharia principles such as; prohibition of usury, maysir and gharar. This article describes the basic concepts, objectives, operational systems of service delivery, risk management, and fund collection and distribution systems used by IFIs. This study uses a descriptive approach with qualitative analysis methods to obtain patterns and themes in the operational management practices of IFIs. The results show that Islamic financial institutions have unique characteristics that distinguish them from conventional financial institutions with implications for the application of sharia principles to maintain public trust and promote financial inclusiveness and take a different risk management approach. Recommendations for improving operational efficiency through technology adoption reflect IFIs' commitment to facing challenges and taking advantage of future growth opportunities. This study contributes to a deeper understanding of how IFIs manage their operations effectively, maintain integrity and support inclusive economic growth in Indonesia.